Women and religion in the African diaspora : knowledge, power, and performance - Griffith, R. Marie (Ruth Marie), 1967-; Savage, Barbara Dianne (Lived religions., 2006)
This landmark collection of newly commissioned essays explores how diverse women of African descent have practiced religion as part of the work of their ordinary and sometimes extraordinary lives. By examining women from North America, the Caribbean, Brazil, and Africa, the contributors identify the patterns that emerge as women, religion, and diaspora intersect, mapping fresh approaches to this emergent field of inquiry. The volume focuses on issues of history, tradition, and the authenticity of African-derived spiritual practices in a variety of contexts, including those where memories of suffering remain fresh and powerful. The contributors discuss matters of power and leadership and of religious expressions outside of institutional settings. The essays study women of Christian denominations, African and Afro-Caribbean traditions, and Islam, addressing their roles as spiritual leaders, artists and musicians, preachers, and participants in bible-study groups. This volume's transnational mixture, along with its use of creative analytical approaches, challenges existing paradigms and summons new models for studying women, religions, and diasporic shiftings across time and space.